Post-Covid-19 tourism: perspectives for sustainable tourism in Brazil, USA and Spain - Fontoura, Leandro Martins; Lusby, Carolin; Romagosa, Francesc (REVISTA ACADÊMICA OBSERVATÓRIO DE INOVAÇÃO DO TURISMO, 2020)
This study investigated the impacts of the coronavirus on the tourism industry. Tourism demand during the pandemic was compared in Brazil, Spain and the USA. Implications of the pandemic and the changes on the demand for sustainability in tourism are discussed. Results indicate that although the industry did stop almost entirely, there are opportunities for the revival of a more sustainable tourism.